FABRICATED CUT INJURY TO NECK- A CASE REPORT (Journal of Forensic Medicine & Toxicology, 2013)
This is an unusual case of fabricated cut injury to neck. A 26yr old married lady was found dead in the backyard of her house with cut injury to neck and her jewels were stolen. At autopsy, the cause of death was found to be asphyxia due to cumulative effect of smothering and strangulation. The cut injury to neck was a fabricated one, to divert the case as murder for gain. This case reiterates the importance of thorough and meticulous autopsy with an open mind in all the cases and not just relying on the information furnished by the police.
Keywords: Intimate partner homicide; Strangulation; Smothering; Cut injury to neck